Pertanggungjawaban Pejabat Administrasi Negara Dalam Hal Terjadinya Kerugian Pada Keuangan Negara Dalam Kasus Tindak Pidana Korupsi - Hamzar Nodi (Jurnal Ilmu Hukum, 2013)
Lots of administration officials act committed by state administrative decisions later on declared as a criminal act of corruption because there is evidence that a state administrative decision is causing loss to the economy or finance. Strict limits whether a state administrative officials charged with corruption can be accounted for is the condition or objective factors on the field that if he is to act in accordance with the authority, making policies which is in fact contrary to his authority by laws and regulations.